Normative nasalance scores in Tamil-speaking Indian children. (2nd January 2022) - Pokharel, Apar; Naina, P.; Sebastain, Swapna; Syed, Kamran Asif; John, Mary; Varghese, Ajoy Mathew
Abstract: Objective: The aim of this study was to obtain normative nasalance scores for Indian Tamil-speaking children. Methods: Mean nasalance scores were obtained from 175 consecutive Tamil-speaking normal children (95 males, 80 females) aged 5–16 years during the repetition of six standardized sentences: two oral, two oronasal, and two nasal sentences. The nasal view was used to obtain nasalance scores for the standardized sentences Results: Group mean and standard deviation (SD) nasalance scores of children for oral, oronasal, and nasal sentence were 35.65(SD 7.20), 44.42(SD 7.37), and 57.21(SD 8.15), respectively. The mean nasalance values of children aged 9–12 years were greater than children aged 5–8 years and 13–16 years for nasal sentences ( p < .001). Males were found to have significantly higher nasalance scores for oral and oronasal sentences ( p < .05) although these differences were within the range of normal variation. Conclusions: The present study provides normative nasalance scores for Tamil-speaking Indian children.